Analisis Karakteristik Fisiko-Kimia dan Pengendalian Variabilitas Kualitas Ekoenzim Berbasis Limbah Organik Domestik - ., Maidawati; Yetrina, Mutiara; Sepriana, Rina; ., Susriyati; Harma, Beni (LPPM Universitas Dharma Andalas, 2026)
Waste is one of the problems faced by many countries in the world, including Indonesia. Indonesia is one of the world's largest waste contributor developing countries. Waste can come from restaurants, factories, companies, schools, government agencies, households, etc. Domestic organic waste management is still a serious environmental problem, this is characterized by the high contribution of organic waste to national waste generation and limited capacity of landfills. Ecoenzymes are one of the alternative approaches developed in the use of organic waste. However, the development of ecoenzymes towards a wider production scale still faces the main challenge in the form of product quality variability, especially related to the stability of physico-chemical properties. This study aims to analyze the physico-chemical characteristics and variability of the quality of the eco-economy based on fruit, vegetable, and mixed waste materials as the basis for quality control and process stratification The study method used an experimental design with three treatments of 1:3:10 (sugar:waste:day) for 90 days under anaerobic conditions. The quality parameters analyzed included acidity (pH) and turbidity (NTU), which were measured using a digital pH meter and a calibrated turbidimeter. The data were analyzed statistically descriptively. The results showed that fruit-based ecoenzymes produced a lower and more stable pH (average 3.21 ± 0.15) compared to vegetable waste (average 3.9 ± 0.42). The turbidity level is low (<15 NTU), while vegetable waste produces a higher pH (3.95 ± 0.42) with high turbidity (< 50 NTU). From an industry perspective, vegetable-based ecoenzymes demonstrate the need for stricter process control and standardization to ensure product consistency in mass production.